Integration of Information about Environment News - Sri Meylan Mantali; Noval Sufriyanto Talani; Yowan Tamu (Laboratorium Riset Ekonomi, 2023)
This study discusses how information about the environment is related to students' attitudes toward protecting the environment. If the information has valence and credibility, then the information will influence individuals to believe in the events conveyed in the information. Individuals can believe, then take a stand to reject or accept the things that are being told in the information. Valance and credibility are under the theory of information integration. This research was conducted with a qualitative approach and data collection techniques through in-depth interviews. The results of this study show that Communication Science students at UNG choose to receive information through digital media rather than visual, audio, and audiovisual media. It means digital media's value and credibility are more robust than traditional media. Communication Science students also have qualified and high knowledge related to environmental issues. However, students need the behavior to maintain the integrity of nature and protect the environment. Students already have more than enough knowledge about protecting the environment.